Clinical Response to Sorafenib in a Patient with Metastatic Colorectal Cancer and FLT3 Amplification - Raphael Brandão Moreira; Renata D''Alpino Peixoto; Marcelo Rocha de Sousa Cruz (Case Reports in Oncology, 2015)
Background: A considerable number of patients with metastatic colorectal cancer progress after exhausting all approved standard therapies but maintain an adequate performance status and could be candidates for further treatment. We aim at reviewing our experience with sorafenib treatment of a patient with FLT3 mutation in refractory metastatic colorectal cancer. Methods: Treatment with sorafenib of a patient with metastatic colorectal cancer and FLT3 translocation who had previously been heavily treated. Results: The patient with metastatic colorectal cancer, aged 51 years, showed significant symptomatic and laboratory improvement with sorafenib treatment (400 mg twice daily). Conclusion: The presented case illustrates how an aggressive and refractory colorectal tumor may respond well to targeted therapy.